Health-related Problems of People travelling to Countries in Different Climatic Zones - preliminary report - Van Damme-Ostapowicz, Katarzyna; Krajewska-Kułak, Elżbieta; Flisiak, Robert; Mięgoć, Henryka; Kowalczuk, Krystyna (Nursing in the 21st Century, 2012)
HEALTH-RELATED PROBLEMS OF PEOPLE TRAVELLING TO COUNTRIES IN DIFFERENT CLIMATIC ZONES - PRELIMINARY REPORTIntroduction. Currently, the mobility of humans between continents is increasingly common. The world is sometimes referred to as a global village, and travels to tropical countries are more and more popular. Many Polish citizens travel every year to the tropics, and the vast majority of them have no knowledge of health-related risks associated with their country of destination. That fact translates into the necessity to draw attention to travel-related problems and to a professional attitude that can prevent many diseases, disability and the dangerous spreading of diseases in a society, and even patients’ death.Aim. The purpose of the study was the self-evaluation of the physical health condition of 40 individuals who returned from a country located in a different climatic zone.Material and methods. The study was conducted on a group of 40 patients of the Clinic of Tropical Diseases in the Department of Contagious Diseases and Hepatology of the Medical University in Białystok in 2009/2010, based on a survey questionnaire developed for that purpose by the authors.Results. The majority of respondents declared the following risky behaviour during their travel abroad: eating “local specialities” of unknown origin (88%), drinking beverages on ice (90%) and brushing teeth using tap water (43%). Stomach-related problems of the surveyed (87%) had already started during their travel. Five of them had taken anti-malaria drugs and reported the following associated ailments: dizziness, nausea, tiredness, hallucinations.Almost all respondents (95%) declared that they had drunk at least 2 litres of water a day. Majority of the surveyed (90%) sunbathed, regardless the time of a day. Cosmetics with UV shield were used by 85% of the surveyed, and all of them (100%) declared wearing hats and sunglasses. First grade sunburn was reported by 45% of the surveyed.Conclusion. Patients returning home from countries located in different climatic zones reported complaints associated with traveller’s diarrhoea, sunburn, and use of anti-malaria chemo-prophylactics. Obtained results may suggest that those patients had no sufficient knowledge with regard to health protection related to travels to countries located in different climatic zones and with low living standards.